STUDI KASUS DALAM MENANGGULANGI KENAKALAN REMAJA MELALUI KOMUNIKASI KELUARGA - Muliaty Amin; Muh. Shuhufi; Muh. Arif (Universitas Islam Negeri Alauddin Makassar, 2019)
This study discusses the family communication strategy in overcoming juvenile delinquency (motorcycle gang case study) in Manuba Village, Mallusetasi Subdistrict, Barru Regency, with the main problem is how the family communication strategy is used to tackle juvenile delinquency (motorcycle gang case study) and what are the inhibiting factors communication strategy for families in overcoming juvenile delinquency in Manuba Village, Mallusetasi Subdistrict, Barru Regency. Data analysis techniques, data reduction, data display and conclusion. The results showed that the strategy of family communication in overcoming juvenile delinquency in Manuba Village, Mallusetasi Subdistrict, Barru Regency was face-to-face communication with dialogue/discussion methods, role models and habits, attention and methods of advice. The barriers to communication between parents and adolescents are internal and external barriers. Internal barriers are personality factors while external barriers are environmental factors of society and excessive use of cell phones.